Efficient tone detection solutions using programmable logic devices - Jaquenod, Guillermo A.; Villagarcía Wanza, Horacio Alfredo; De Giusti, Marisa Raquel (2003)
Digital solutions have been used for many years in central office and private automated branch exchange (PABX) designs. Although many functional blocks are available (ASICs or DSP solutions), only a few programmable logic solutions are known. Within a PABX and over E1 or T1 trunks, signals are digitized samples of audio, both for voice and signaling purposes. Dual Tone Multi Frequency (DTMF) is a standard where keystrokes from the telephone keypad are translated into dual tone signals over the audio link. Additionally, On/Off modulation of a 425 Hz signal, is used to identify the Call Progress Status (CPS): Dialing, Ringing, etc.. Special algorithms must be run to decode these signals, not only to detect the presence of tones, but also to ensure that voice signals can't be misdetected as DTMF. This paper describes a DTMF/CPS numeric coprocessor for detection task implemented using programmable logic devices (PLD). The same architecture, with different parameters, can be used to process other tone standards, such as ITU- R2 signaling.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca.) -- Disponible también en línea (Cons. 10/07/2014)
Workshop IBERCHIP (9º : 2003 mar. 26-28 : La Habana)
Keywords: CIRCUITOS INTEGRADOS; ESTÁNDARES; DISPOSITIVOS DE ENTRADA/SALIDA; PROGRAMACIÓN LÓGICA